Methanogen community composition and rates of methane consumption in Canadian High Arctic permafrost soils. Issue 2 (23rd January 2014) - Allan, J.; Ronholm, J.; Mykytczuk, N. C. S.; Greer, C. W.; Onstott, T. C.; Whyte, L. G.
Summary Increasing permafrost thaw, driven by climate change, has the potential to result in organic carbon stores being mineralized into carbon dioxide (CO2) and methane (CH4) through microbial activity. This study examines the effect of increasing temperature on community structure and metabolic activity of methanogens from the Canadian High Arctic, in an attempt to predict how warming will affect microbially controlled CH4 soil flux. In situ CO2 and CH4 flux, measured in 2010 and 2011 from ice‐wedge polygons, indicate that these soil formations are a net source of CO2 emissions, but a CH4 sink. Permafrost and active layer soil samples were collected at the same sites and incubated under anaerobic conditions at warmer temperatures, with and without substrate amendment. Gas flux was measured regularly and indicated an increase in CH4 flux after extended incubation. Pyrosequencing was used to examine the effects of an extended thaw cycle on methanogen diversity and the results indicate that in situ methanogen diversity, based on the relative abundance of the 16S ribosomal ribonucleic acid (rRNA) gene associated with known methanogens, is higher in the permafrost than in the active layer. Methanogen diversity was also shown to increase in both the active layer and permafrost soil after an extended thaw. This study provides evidence that although High Arctic ice‐wedge polygons are currently a sink for CH4, higher arctic temperatures and anaerobic conditions, a possible result of climate change, could result in this soil becoming a source for CH4 gas flux.